Numerical calculation of a 20MN heavy duty hydraulic press for analyzing the double frame pre-stressed steel wire winding - Zhang, Yumin; Wang, Xigui; Wang, Yongmei (Frontiers in Mechanical Engineering, 2023)
The expected preloading effect of a hydraulic press frame parts (upper/lower semi-circular beams and columns) with pre-stressed by means of Winding Steel Wires (WSW), which is directly related to the reliability and normal safe operation of the hydraulic press. The deformation of the Hydraulic Press Column (HPC) is an important indicator of the optimal preloading effect of the hydraulic press. A novelty of this project is to break through a bottleneck technology, the continuous cumulative deformation of a HPC under seven time-varying steps is critical issues especially in theoretically calculated for a 20MN double-frame hydraulic press with pre-stressed using WAW. A solid model with a pre-stressed frame is pre-designed by 3D software, and two simulation methods, equivalent pressure loading and equivalent temperature loading, are used to simulate and analyze the continuous cumulative deformation of the HPC under each step in Ansys Workbench software. By comparing the deformation and error analysis in the three cases above, the feasibility of the two simulation methods is verified, which leads to the advantages and disadvantages of each method in order to guide the subsequent design.